Detection of Rare Weaker A Subgroup: Aend - Tamanna Afroz (Global Journal of Transfusion Medicine)
Subgroups of A are very rare phenotypes. Weaker subgroups give rise to discrepancies between forward and reverse grouping. Conventional methods could misread these rare and weak subgroups occasionally. Weaker A subgroups that have been reported so far are mainly A3, Ax, Aend, Am, Ay, and Ael. Here, we report one interesting case of a rare weaker A subgroup in a patient who was wrongly typed as Group O. After performing the initial blood grouping, a detailed analysis was done including absorption elution tests and saliva tests. The serological characteristics of the patient’s red cells were similar to the Aend subtype. The patient was a secretor having only H substance. Anti-A1 was absent in the serum. This report highlights the importance of routine forward and reverse grouping in solving blood group discrepancy.